Postpartum Intrauterine Device Refusal in Delhi: Reasons Analyzed - Nigam, Aruna (J Obstet Gynaecol India, 2015)
AIM: To assess knowledge and attitude of women toward postpartum intrauterine contraceptive device (PPIUCD) and analyze reasons of refusal. SETTING AND DESIGN: Hospital-based cross-sectional study for 1 year. MATERIALS AND METHODS: 550 women were enrolled in the study. Sociodemographic characteristics, knowledge, and attitude toward contraception especially PPIUCD were noted, and the reasons for refusal of PPIUCD were analyzed. STATISTICAL ANALYSIS: SPSS version 17.0 is used. Continuous variables were reported using mean, and categorical variables were reported using percentages. OBSERVATIONS: PPIUCD insertion rate was 9.1 %. 78.6 % of women in the study belonged to the age group of 20–30 years, with 79.2 % having education of Class X and above. The overall contraceptive knowledge was 94.4 %. Although 48.4 % women were aware of Cu T as a method of contraception, only 21.9 % of 48.4 %, however, were aware of PPIUCD. None of the women had ever used it before. The commonest prevalent myths regarding Cu T were fear of malignancy (38 %) and fear of menorrhagia (36.4 %). The husband and mother-in-law played important roles in decision regarding PPIUCD insertion and refused the same in 59 % of cases. CONCLUSION: The study shows that awareness of PPIUCD is low in this region despite good education, leading to high refusal rates. The commonest reason is lack of appropriate counseling, and not only the woman but the husband and mother-in-law also must be provided the knowledge of it as they play important roles in our society.